A ‘torn bag mechanism’ of small extracellular vesicle release via limiting membrane rupture of en bloc released amphisomes (amphiectosomes) - Tamás Visnovitz; Dorina Lenzinger; Anna Koncz; Péter M Vizi; Tünde Bárkai; Krisztina V Vukman; Alicia Galinsoga; Krisztina Németh; Kelsey Fletcher; Zsolt I Komlósi; Csaba Cserép; Ádám Dénes; et al. (eLife)
Recent studies showed an unexpected complexity of extracellular vesicle (EV) biogenesis pathways. We previously found evidence that human colorectal cancer cells in vivo release large multivesicular body-like structures en bloc. Here, we tested whether this large EV type is unique to colorectal cancer cells. We found that all cell types we studied (including different cell lines and cells in their original tissue environment) released multivesicular large EVs (MV-lEVs). We also demonstrated that upon spontaneous rupture of the limiting membrane of the MV-lEVs, their intraluminal vesicles (ILVs) escaped to the extracellular environment by a ‘torn bag mechanism’. We proved that the MV-lEVs were released by ectocytosis of amphisomes (hence, we termed them amphiectosomes). Both ILVs of amphiectosomes and small EVs separated from conditioned media were either exclusively CD63 or LC3B positive. According to our model, upon fusion of multivesicular bodies with autophagosomes, fragments of the autophagosomal inner membrane curl up to form LC3B positive ILVs of amphisomes, while CD63 positive small EVs are of multivesicular body origin. Our data suggest a novel common release mechanism for small EVs, distinct from the exocytosis of multivesicular bodies or amphisomes, as well as the small ectosome release pathway.